GPS Velocity and Strain Rate Fields in Southwest Anatolia from Repeated GPS Measurements - Erdogan, Saffet; Sahin, Muhammed; Tiryakioglu, Ibrahim; Gulal, Engin; Telli, Ali Kazim (MDPI, 2009)
Southwestern Turkey is a tectonically active area. To determine kinematics and strain distribution in this region, a GPS network of sixteen stations was established. We have used GPS velocity field data for southwest Anatolia from continuous measurements covering the period 2003 to 2006 to estimate current crustal deformation of this tectonically active region. GPS data were processed using GAMIT/GLOBK software and velocity and strain rate fields were estimated in the study area. The measurements showed velocities of 15-30 mm/yr toward the southwest and strain values up to 0.28-8.23x10(-8). Results showed that extension has been determined in the Burdur-Isparta region. In this study, all of strain data reveal an extensional neotectonic regime through the northeast edge of the Isparta Angle despite the previously reported compressional neotectonic regime. Meanwhile, results showed some small differences relatively with the 2006 model of Reilinger et al. As a result, active tectonic movements, in agreement with earthquake fault plane solutions showed important activity.
Keywords: Burdur-Fethiye fault zone; GPS; strain; CRUSTAL DEFORMATION; ISPARTA ANGLE; SW TURKEY; CONSTRAINTS; KINEMATICS; SLIP; Chemistry; Engineering; Instruments & Instrumentation